A 4.8-kW high-efficiency 1050-nm monolithic fiber laser amplifier employing a pump-sharing structure - Meng, Xiangming; Li, Fengchang; Yang, Baolai; Ye, Yun; Chai, Junyu; Xi, Xiaoming; Wang, Peng; Wu, Hanshuo; Shi, Chen; Zhang, Hanwei; Wang, Xiaolin; Han, Kai (Frontiers in Physics, 2023)
The power scaling of ytterbium-doped fiber (YDF) lasers emitting at the wavelength range of 1030 nm -1060 nm has been limited by amplified spontaneous emission (ASE), stimulated Raman scattering (SRS) effect and transverse mode instability (TMI). These effects pose challenges in achieving a highoutput power laser within the range of 1030 nm -1060 nm, while maintaining a high signal-to-noise ratio. Based on a counter-pumped fiber laser amplifier utilizing our self-developed ytterbium-doped fiber, we have successfully showcased a 4.8 kW laser output at 1050 nm, accompanied by an 85.3% slope efficiency and nearly diffraction-limited beam quality. By effectively ASE and TMI, and controlling the Raman Stokes 17 dB below the primary signal wavelength, we have achieved optimal performance at the maximum power level. This high efficiency has been attained through a pumpsharing structure combined with cost-effective, non-wavelength-stabilized 976 nm laser diodes.